2020
DOI: 10.24018/ejfood.2020.2.6.138
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Financial Literacy of Farmers Food Crops in the Poor Area of Madura, Indonesia

Abstract: An effort to encourage increased food productivity is directly proportional to the limited access of farmers on capital financing resources. The purpose of the research is to describe the financial literacy rate of farmers in Madura. The data analysis method uses a descriptive (qualitative) analysis and a different test (T-Test) with IBM SPSS. 23 Software support. The results of the research obtained that food farmers in Sampang and Bangkalan districts have a relatively moderate financial knowledge with all it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Widhiyanto et al (2018) reported a moderate level of FL amongst the Indonesian farmers and age, education, distance to the national capital, income, bank account, and financial education were noted as the important factors affecting the level of FL. Such a moderate level of FL was also observed by Santoso et al (2020) and Safitri (2021) in respect of Indonesian farmers. Lakkanawanit and Dungtripop (2018) also showed that age, education and practice of book keeping were found to exert a significant positive effect on the moderate level of FL amongst the rice growers in the PakPanang basin of Thailand.…”
Section: Brief Literature Reviewsupporting
confidence: 51%
See 3 more Smart Citations
“…Widhiyanto et al (2018) reported a moderate level of FL amongst the Indonesian farmers and age, education, distance to the national capital, income, bank account, and financial education were noted as the important factors affecting the level of FL. Such a moderate level of FL was also observed by Santoso et al (2020) and Safitri (2021) in respect of Indonesian farmers. Lakkanawanit and Dungtripop (2018) also showed that age, education and practice of book keeping were found to exert a significant positive effect on the moderate level of FL amongst the rice growers in the PakPanang basin of Thailand.…”
Section: Brief Literature Reviewsupporting
confidence: 51%
“…(2018) reported a moderate level of FL amongst the Indonesian farmers and age, education, distance to the national capital, income, bank account, and financial education were noted as the important factors affecting the level of FL. Such a moderate level of FL was also observed by Santoso et al. (2020) and Safitri (2021) in respect of Indonesian farmers.…”
Section: Brief Literature Reviewsupporting
confidence: 51%
See 2 more Smart Citations
“…Akoto et al (2017) and Twumasi et al (2021) observed the prevalence of poor FL (affected by age, economic status, educational attainment, gender, risk tolerance and viewership of FL television programmes) amongst Ghanaian farmers. On the other hand, Widhiyanto et al (2018), Santoso et al (2020) and Safitri (2021) noticed that the moderate FL amongst the Indonesian farmers geting affected by age, educational attainment, level of income, financial inclusion (FI) and FL training. Similarly, Lakkanawanit and Dungtripop (2018) also noticed a moderate level of FL (affected by age, education and habit of practicing book-keeping) amongst the rice cultivators of Thailand.…”
Section: Brief Review Of Literaturementioning
confidence: 99%